Bertafsir Ala Schleiermacher - Mus'idul Millah; Hikmatul Luthfi (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2021)
It is undeniable that as one of the sources of Islamic teachings, hadiths have both the authority and the problems that have been dynamically studied until now. The development of hadith studies is not only in demand by Muslims but also non-Muslims who are often represented as West. The study of the authenticity and the authority of hadith are the two focuses of early studies that have caused heated debates between scholars and orientalists, as well as the munkir al-sunnah. At present, the study of hadith interpretation and living sunnah are areas of hadith study that are getting more attention. In the aspect of the interpretation of hadith, hermeneutic is considered to be an alternative method that can provide new interpretations because it is carried out with various existing scientific approaches. Thus, the meaning of hadith is no longer dominated by linguistic and Islamic approaches, but also social and scientific approaches with the hope of being able to answer actual problems in society. Of course the projected application of hermeneutics must be studied intensively and continuously. And this article will examine the application of psychological hermeneutics and grammatical hermeneutics proposed by Schleiermacher in the hadith about patience in facing trials, to see the conceptual similarities between hermenerutics and the science of hadith and the appropriateness of their use in understanding hadith. Abstrak Tidak dapat dipungkiri bahwa sebagai salah satu sumber ajaran Islam, hadis memiliki otoritas sekaligus ‘permasalahan’ yang sampai saat ini terus dikaji secara dinamis. Perkembangan kajian hadis juga tidak hanya diminati oleh kalangan Muslim tapi juga Non-Muslim yang kerap direpresentasikan sebagai Barat. Kajian mengenai autentisitas dan otoritas hadis merupakan dua fokus kajian awal yang pernah menimbulkan perdebatan sengit antara para ulama dan orientalis, begitu juga dengan golongan munkir al-sunnah. Saat ini, kajian syarah hadis dan living sunah merupakan bidang kajian hadis yang mendapatkan atensi lebih. Dalam aspek pemaknaan hadis, hermeneutika dianggap bisa menjadi metode alternatif yang bisa memberikan interpretasi baru karena dilakukan dengan berbagai pendekatan keilmuan yang ada. Dengan demikian, pemaknaan hadis tidak lagi didominasi oleh pendekatan kebahasaan dan keislaman semata, tetapi juga pendekatan sosial dan saintifik dengan harapan mampu menjawab permasalahan aktual di tengah masyarakat. Tentu saja proyeksi penerapan hermeneutika dalam kajian keislaman harus dikaji secara intens dan berkelajutan. Dan artikel ini akan mengkaji aplikasi hermeneutika psikologis dan hermeneutika gramatikal yang digagas oleh Schleiermacher pada hadis tentang sabar, untuk melihat kesamaan konseptual antara hermenerutika dan Ilmu Hadis dan kelayakan penggunaannya dalam memahami hadis.